The Viability of Islamic Estate Planning in Malaysian Muslim Market: A Bibliometric Analysis Indexed by Scopus from 2015 to 2021 - Muhamad Mu'izz Abdullah; Naimah Mohamad Nasir; Nurul Fadly Habidin (USIM Press, 2024)
Journal of Muamalat and Islamic Finance Research Vol. 20, No. 1, Page (1-23)